Teaching Patients About Pain: The Emergence of Pain Science Education, its Learning Frameworks and Delivery Strategies - Lorimer Moseley, G; Leake, Hayley B; Beetsma, Anneke J; Watson, James A; Butler, David S; van der Mee, Annika; Stinson, Jennifer N; Harvie, Daniel; Palermo, Tonya M; Meeus, Mira; Ryan, Cormac G (The journal of pain, 2024)
Since it emerged in the early 2000's, intensive education about 'how pain works', widely known as pain neuroscience education or explaining pain, has evolved into a new educational approach, with new content and new strategies. The substantial differences from the original have led the PETAL collaboration to call the current iteration 'Pain Science Education'. This review presents a brief historical context for Pain Science Education, the clinical trials, consumer perspective, and real-world clinical data that have pushed the field to update both content and method. We describe the key role of educational psychology in driving this change, the central role of constructivism, and the constructivist learning frameworks around which Pain Science Education is now planned and delivered. We integrate terminology and concepts from the learning frameworks currently being used across the PETAL collaboration in both research and practice-the Interactive, Constructive, Active, Passive framework, transformative learning theory, and dynamic model of conceptual change. We then discuss strategies that are being used to enhance learning within clinical encounters, which focus on the skill, will, and thrill of learning. Finally, we provide practical examples of these strategies so as to assist the reader to drive their own patient pain education offerings towards more effective learning. PERSPECTIVE: Rapid progress in several fields and research groups has led to the emergence 'Pain Science Education'. This PETAL review describes challenges that have spurred the field forward, the learning frameworks and educational strategies that are addressing those challenges, and some easy wins to implement and mistakes to avoid.